The Oniad Sibyl how a Greek prophetess became a revolutionary mouthpiece for Egyptian Jews - Vargas, Miguel M. (Leiden Boston Brill, 2025)
"The Oniad community was a mercenary and priestly Jewish settlement in Greco-Roman Egypt. This community recognized an exiled high priest of the Jerusalem Temple as its founder and met its end after a Mediterranean-wide uprising that shook the foundations of the Roman Empire. This monograph attributes a group of rather puzzling prophetic narratives-filled with coded language, reused lines from Greek and Jewish literature, and confused historical references-to the Oniads. The thesis of this study is that each prophetic treatise responds to crises experienced by the Oniad settlement and, as a result, evidences its unfolding historical consciousness and hybrid literary culture in distinct phases of its existence"--
A Jewish Sibyl and the Oniads of Egypt -- Oracular diviniation in the Ancient Mediterranean -- Oracula Sibyllina -- Oracula Sibyllina -- Oracula Sibyllina -- The Oniad Sibyl.
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Temple of Onias (Qalyūbīyah, Egypt); Oracula Sibyllina; Prophecy -- Judaism; Sibyls -- Mediterranean Region; Diviniation -- Mediterranean Region; Jews -- Egypt -- Leontopolis (Qalyūbīyah : Extinct city); Leontopolis (Qalyūbīyah, Egypt : Extinct city) -- Antiquities